Efektivitas Pengunaan Channel Youtube @institutstiamiofficial Sebagai Media Penyebaran Informasi Pada Mahasiswa Manajemen Komunikasi di Institut Ilmu Sosial dan Manajemen STIAMI - Sahrullah, Fachry; Yonavilbia, Eka (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Youtube is the First Order social media with users most in Indonesia, on Youtube there are several channels become a source of information for students, one of which is Youtube channel @institutstiamiofficial. Youtube Channel @institutstiamiofficial the majority of users are students. The purpose of this study to determine the effectiveness of the use of Youtube channel @institutstiamiofficial as a medium of information dissemination on communication management student at the Institute of Social Sciences and management Stiami. This study uses the theory of Uses and Gratification of Blumer & Katz (2018) with qualitative descriptive methods. Technique data collection used in this study is observation, documentation and interviews. Subject in this study students Communication Management who owns Youtube and have access and see impressions from the channel @institutstiamiofficial. Results of this study, 1) the effectiveness obtained from the Youtube channel @institutstiamiofficial still less effective because there is information monotonous, unscheduled show times, and the number of subscribers which is very little, 2) the barriers experienced in using Youtube channel @institutstiamiofficial barriers in delivering information via Youtube channel @institutstiamiofficial is a problem technical and limited information available on this Youtube channel, 3) the solution is to maintain active involvement in creating creative content on the Youtube platform and sharing information related lectures.